Budaya Hukum llmuwan tentang Hak Cipta: Suatu Penelitian Hukum Empiris - Muhammad Syamsudin (Fakultas Hukum Universitas Islam Indonesia, 2002)
This writing is aimed to discuss either theoretically or empirically about the cultural law of scientist for copyright. The cultural law has a very large meaning, covers the vaiues, ideas, knowledge, belief, attitude and societal behaviour to the law both positive andnegative. In this writing, the law values and societal behaviour of the law becomes an indicator inknowing the law culture. Statistics isapplied to assist analyzing the main data gained from the research subject, namely the scientists at the universities in Yogyakarta more about 114 which they are gained in a quata way. In the analysis, itis used an CHI square by using the three category of law culture, namely strong, middle andweak. The result shows that thelaw culture of scientists on copyright in general are strong enough which is showed by the value indicator and positive behaviour on the Acts of Copyright. It means that in the scientist environment, the Act of Copyright is well understood, comprehended and held by the scientist in doing their scientific activities. The Acfs ofCopyright also gives gurantee of justice, exactness and utility for the scientist dealwith scientific paper.